The Effect Of Teacher Performance On Academic Achievement Of Elementary School - Fadlun Fadlun; Erni Fatmawati (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2023)
This study aims to determine the effect of Teacher Performance on Academic Achievement of Elementary School Students. This research is a mix methode research. The population in this study were 66 teachers and 189 students. Collecting data using a questionnaire, then analyzed using simple regression techniques and multiple regression. The results of this study that is Teacher performance has a positive influence on the Academic Achievement of Class Students, as evidenced by the value of Sig = 0.005 < = 0.050, while the value of the correlation coefficient (r2) = 0.116 or only contributes 11.6%. Teacher performance plays a role in improving student academic achievement.